Propaganda and ideological representation of women in The Secret of Women (2014) and Maleficent (2014) - Yahya Mohammed, Estabraq; Vafa, Amirhossein (Research Journal in Advanced Humanities, 2024)
The paper compares female representation in two selected films, The Secret of Women and Maleficent, released in 2014. The aim is to show the influence of cinema on shaping and commercializing female protagonists' identities. The films are affected by the geopolitical context of Iraq/America. The Secret of Women, set in the 1950s, delves into the complex experience of females and celebrates their strength, knowledge, and persistence. Maleficent displays the determination and compassion of the main protagonist. The findings indicate that these two films support a more positive ideology and avoid traditional gender roles and stereotypes. The Secret of Women empowers Manahil by giving her a strong voice, highlighting the communist and tribal issues of her time. In the same way, Maleficent deviates from the conventional representation of strong women by analyzing the themes of salvation, the conflict between matriarchy and patriarchy, and women's empowerment. The results enhance the continuing discourse on gender representation in films and the capacity for cinema to question cultural norms and perspectives toward women.